Association of N and E Genes with ORF1b Gene for Early Detection of COVID-19 in Pakistani Patients - Waryah, Yar Mohammad; Ehsan , Shaista; Nigar , Roohi (Journal of Liaquat University of Medical & Health Sciences, 2023)
Objective: To investigate the role of the first line and additional confirmatory assay to detect coronavirus based on Ct RT-PCR values. Methodology: A collaborative cross-sectional study was conducted using a systematic sampling type at Hyderabad’s diagnostic and research laboratory and the SIOVS, Hyderabad, after getting ethical approval from the LUMHS ERC committee from July 2021 to June 2022. A total of 4822 patients have enrolled; 1200 patients were positive for COVID-19, and a nasopharyngeal swab was collected from patients for RNA extraction; the patients positive with COVID-19 RT-PCR test were included, and patients negative with COVID-19 RT-PCR were excluded out from this study. The RT-PCR was performed, and the Ct values of each potential target were recorded. Results: The RT-PCR finding of potential targets revealed that the N and E genes are correlated and simultaneously positive with OFRb1 and RdRP genes and are crucial for detecting coronavirus. In 77.5% (310/400) of patients, the E gene was positive, and the N gene was positive in 85.8% (1030/1200) patients with ORF1b and Rdrp genes. 71% (850/1200) of males were infected in our cohort, and young patients carried the highest viral load than old age patients with asymptomatic features. Each target’s obtained cycler threshold values by different kits were recorded and analyzed in SPSS-17. Conclusion: The data showed N and E genes are simultaneously associated with the ORFb1 gene for detecting COVID-19 in our patients.